Produção de inóculo e sobrevivência de Sclerotinia sclerotiorum - Brustolin, Ricardo (2012)
The white mold of soybean caused by Sclerotinia sclerotiorum (Ss), has become an important disease in different growing regions of Brazil, especially in those with favorable environment, causing losses to the Brazilian agribusiness. The experience of other countries who live with this pathogen is of fundamental importance for Brazil, but we need to know the behavior of isolates from the countryl, to direct management strategies according to different production systems. Thus the objectives of this study were to: (i) determine the best method for sclerotia production, (ii) determine the best method to induce carpogenic germination (iii) quantify the longevity of sclerotia produced in soybean; ( iv) develop a methodology for artificial inoculation of soybean seeds and quantify the transmission to stems via the cotyledons, and the formation of sclerotia in the soil by the mycelium colonizing the seeds. The experiments were conducted at the University of Passo Fundo during the years 2011 to June 2012. Four methods for sclerotia production in different nutritive substrates, added or not to corn flour (CF) were compared. These sclerotia were selected, together with those formed on the PDA medium and with carpogenic gemination and the greatest number of apothecia by sclerotia, in sand substratum saturated with water when compared to the water-agar (A/A). In the longevity test the sclerotia were exposed to field conditions and their viability determined at a monthly intervals, where those that germinated producing apothecia were considered viable. For artificially seed infection seeds were exposed to Ss mycelium for four times (12, 24, 36 and 48 hours). Infected seed was identified by plating on NEON-S medium and used in growth chamber and in the field work to quantify the cotiledonary transmission by the presence of lesions and sclerotia formation by non-germinated seeds. The best methods for sclerotia production were wheat grains mixed with coarse perlite with and without the presence of CF. These sclerotia were selected, together with those formed on the culture medium, and that germinated carpogenically with a great total number of apothecia per sclerotia, on the sand saturated with water when compared to the substrate water-agar (A/A). In the longevity experiment in the field, it was shown that sclerotia deposited on the soil surface, simulating the no till system, lost their viability after 12 months. Soybean seeds can be artificially inoculated with 48 hours of exposure to the fungus mycelium in Petri dishes. It was shown that infected seeds do not germinate when seeded in the soil, and they can form up to 2.18 sclerotia per seed in a controlled environment nevertheless, in the field, sclerotia were not formed due to water deficit. Both in growth chamber and in the field, cotiledonary transmission was not proved.